THE EFFECT OF ACCOUNTABILITY AND TRANSPARENCY OF VILLAGE FUND MANAGEMENT - Ladewi, Yuhanis; Supriadi, Taufiq; Sjam, Juska Meidy Enyke; *, Welly; *, Agista; Subowo, Hery (The International Journal of Accounting and Business Society, 2020)
ABSTRACT Purpose — The purpose of this study is to investigate and analyze the Effect of Accountability and transparency on the management of survey village funds in Merapi Selatan District and Pulau Pinang District, Lahat Regency. This research was conducted because there are phenomena associated with accountability and transparency in the management of village funds.Design/methodology/approach — The methodology used in this study consists of the type of this research is descriptive and associative research. The variables in this study are Accountability, Transparency, and Village Fund Management. The population in this study were 23 villages in Merapi Selatan and Pulau Pinang Districts, each village consisting of 3 respondents. Total questionnaires were distributed as many as 69 questionnaires, because there are some limitations of the questionnaire returned as many as 33 questionnaires and were processed.Findings — Based on the results of research conducted on all data obtained in 33 respondents in Merapi Selatan District and Pulau Pinang District, it was found that accountability significantly affected village fund management, while transparency did not significantly influence village fund management.Practical Implications — This research shows that accountability determines each activity and the final results of village government implementation activities must be accountable to the village community in accordance with statutory provisions. Originality/value — The test used in this research is the validity test, the reliability test, the classic assumption test, the hypothesis test, and the coefficient of determination test.Keywords — village fund management, accountability, transparency.